Aditivo fitogênico na alimentação de novilhas leiteiras da raça Jersey: parâmetros zootécnicos, hematológicos e comportamentais - Gabbi, Alexandre Mossate (2004)
This experiment evaluated the effects above performance, hematological and behavior parameters of phytogenic additive included in feeding of Jersey dairy heifers. The experiment was conducted in Boapaba Ranch, with geographic localization 29º 37 S 53º 30 W, within July to September, 2004, utilizing 12 Jersey s heifers, with mean age and weight at start of trial of eight months and 112 kg, respectively. The animals were separated in two groups, with same number of repetitions, considered a Control group (with addition of phytogenic additive) and a Treatment group (with inclusion of 500 grams of phytogenic additive per ton. of ration). The phytogenic additive utilized was Fresta® F Conc., a commercial blend of essential oils, flavonoids and mucilage. The animals received, daily, divided in two feeding, 2 kg. of ration and, approximately, 3 kg. of alfalfa hay and 10 kg. of chopped black oat and ryegrass. The performance parameters evaluated were initial weight, final weight, daily average daily weight gain and feed conversion of ration. The hematological parameters evaluated were erythrogram and leukogram. Behavior parameters analyzed were feeding behavior, rectal temperature, cardiac beat, and time of intake for ration and roughage. There were not significantly differences (P > 0.05) for performance parameters. Within hematological parameters were observed significantly differences to erythrocytes and monocytes (P < 0.10), lymphocytes (P < 0.05) and leukocytes (P < 0.01). Within behavior parameters, were observed significantly differences to feeding behavior (P < 0.05), cardiac beat (P < 0.05) and time of intake for concentrate (P < 0.01). It is concluded what phytogenic additive act above hematological and behavior parameters of dairy heifers receiving this supplement.